Clinical Profile of Febrile convulsion among admitted children in a tertiary care hospital at Dhaka city - Biswas, Rabi; Munsi, Abu Sayed; Rahman, Md Maksudur; Begum, Nasreen; Das, Rajib Chandra (Northern International Medical College Journal, 2015)
Background : Febrile convulsion (FC) is the most common type of seizure that occurs in children aged 4-60 months, which is benign and had a good prognosis. Objective : To evaluate the clinical profile and management of hospitalized children with Febrile convulsion. Methodology : This cross sectional study was done in Dhaka Shishu (children) Hospital during July 01, 2013 to June 30, 2014. Total 80 children aged between 4-72 months who were admitted in to Pediatric Medicine department with diagnosis of FC were purposively recruited in the study. Data were collected by a trained physician from history, clinical examination, laboratory findings, treatment and outcome using a structured questionnaire. Results : Among the study children 41(51.3%) were between 6 months to 12 months with a male to female ratio was1.5:1. Forty-nine (61.2%) children had simple seizures, and 16 (20%) of the patients had family history of febrile seizures. In 70 (87.5%) cases the duration of seizure was less than 15 minutes and 75% patients had less than one attack within 24 hours of onset of fever. Upper respiratory tract infection was the most common (31%) cause of fever followed by unclassified in 21 (26%) cases. Complete blood count revealed leukocytosis in 49% cases, CRP raised in 30% cases while CSF study and ultrasonography of brain was normal in 30 cases and 10 cases. We could not perform any investigation to isolate possible causative virus. More than 90% per cent received intravenous broad-spectrum antibiotics and prophylactic anticonvulsant drugs during early days of hospitalization. Conclusion : In this study, Upper respiratory Tract infection was found as common cause of febrile convulsion. Duration of seizure was less than 15 minutes and Leukocytosis, raised CRP was identified and nearly all patients received broad-spectrum antibiotics during hospital stay. Northern International Medical College Journal Vol.7(1) Jul 2015: 101-104